Impact of harmonised common balancing capacity procurement in selected Central European electricity balancing markets. (15th July 2018) - Dallinger, Bettina; Auer, Hans; Lettner, Georg
Highlights: Shortening timing and length of balancing products reduces costs, CO2 emissions and RES-E spillage. Short timings and lengths are an appropriate premise to integrate RES-E and DER. DER save millions on top of new balancing market designs. Symmetric procurement of up- and downward balancing is a poor design for RES-E. Co-optimisation of energy and reserve has a noteworthy potential in Europe. Abstract: Contrary to the U.S., where the Independent System Operator is responsible for electricity balancing, in Europe this is the task of Transmission System Operators. Also in terms of market implementation there are fundamental differences between the U.S. (co-optimisation of day-ahead and balancing/ancillary markets) and Europe (separate bidding and clearing in different market segments). This paper focuses on European electricity markets, where recently the framework for upcoming challenges in electricity balancing has been defined ("Network Code on Electricity Balancing"). In detail, different possible (cross-border) balancing market designs in Europe are evaluated using the model EDisOn + Balancing. We focus on the procurement of up- and downward balancing capacity products (conducted jointly or separately), and how common procurement of frequency restoration reserves influences wholesale electricity market clearings. Different timings and lead-times for the procurement of automatically activated frequency restoration reserve are investigated, starting from weekly off-peak and peak products, leading to daily four-hour products. The quantitative results confirm that in addition to asymmetric procurement of up- and downward balancing capacity, common procurement has significant advantages in terms of cost reductions. The shortening of balancing product timings supports the integration of renewable electricity generation essentially. To achieve these positive effects, the first focus should be on harmonising national balancing markets Europe-wide. A best practise case is the pilot project between Germany and Austria: the two countries have already started common activation of automatic frequency restoration reserve and there are plans for future common procurements.